1992
DOI: 10.1002/neu.480230309
|View full text |Cite
|
Sign up to set email alerts
|

Progestin receptors in substance P‐immunoreactive neurons in the hypothalamus of male guinea pigs after behaviorally effective estradiol pulse treatment

Abstract: Pulsatile administration of estradiol effectively primes orchidectomized (ORCH) male guinea pigs to display progesterone-facilitated lordosis. In contrast, a single injection of estradiol benzoate (EB) is not behaviorally effective. In ovariectomized female guinea pigs, estradiol pulses induce progestin receptors selectively in substance P neurons in the ventrolateral hypothalamus (VLH), a site at which estradiol primes females to respond behaviorally to progesterone. To test the hypothesis that behaviorally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The present study shows that SOM is another neuro peptide in the VL whose synthesis may be regulated by progesterone since further immunocytochemical studies have demonstrated the presence of neurotensin [19], sub stance P [21,22] and opiates [23] in the PR-IR neurons of the guinea pig VL. At present we do not know whether these neuropeptides coexist within the same neurons con taining PR or represent separate populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study shows that SOM is another neuro peptide in the VL whose synthesis may be regulated by progesterone since further immunocytochemical studies have demonstrated the presence of neurotensin [19], sub stance P [21,22] and opiates [23] in the PR-IR neurons of the guinea pig VL. At present we do not know whether these neuropeptides coexist within the same neurons con taining PR or represent separate populations.…”
Section: Discussionmentioning
confidence: 97%
“…We found that only a very small fraction of the population of SOM-IR neurons in the Ar possess PR and that neither male nor female preoptic and hypothalamic periventricular SOM Progesterone Receptor in Hypothalamic Somatostatin Neurons neurons contain PR. As such, SOM can now be added to the list of neuropeptides found in PR-IR neurons in the VL of the guinea pig such as neurotensin [ 19] substance P [21,22] and enkephalin [23],…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these steroid sensitive cells in guinea pigs clearly lie outside of the cytoarchitecturally defined ventromedial nucleus. In both rats and guinea pigs, many of the estrogen and progestin receptor-containing neurons in this region, also contain substance P (2,5,6,7). This finding suggests that substance P may be used as a neurotransmitter by these neurons and that its release may be influenced by estradiol and progesterone.…”
mentioning
confidence: 92%
“…Female guinea pigs were exposed to a single injection of E,-17p at a dose similar to that used for injections in pulsatile paradigms which resulted in sex behavior (17)(18)(19)(20). Immunostaining for estrogen receptors in the estrogen receptor-rich areas of the midportion of ventrolateral hypothalamus ( VLH ), caudal portions of the arcuate hypothalamic nucleus (Arc), medial preoptic nucleus (MPO), and the medial amygdaloid nucleus ( M e ) was examined at various time points following the injection.…”
mentioning
confidence: 99%